PENERAPAN PROSEDUR PEMBELAJARAN LITERASI MEMBACA DI SEKOLAH DASAR - Rizqi Latifa, Tiar; Apriliya, Seni; Alia, Dwi (JS (JURNAL SEKOLAH), 2025)
Abstract: Reading literacy learning is based on higher-order thinking skills. This study was conducted in elementary schools with high AKM reading literacy scores and is expected to become a best practice for other schools to learn about reading literacy learning procedures in the field. This study describes the pre-reading, reading, and post-reading stages. The researcher used a qualitative approach with an ethnographic method. Data were obtained through observation and interviews with the principal, teachers, and fifth-grade students. The data were analyzed through reduction, presented thematically, and concluded. Overall, the implementation in the fifth grade of SDN X was not yet fully optimal. The suggestion is for teachers to further develop teaching materials, explore reading strategies, and be consistent in learning reflection. Keyword: Reading Literacy Learning, Procedures, Pre-reading, Reading, Post-reading   Abstrak: Pembelajaran literasi membaca didasarkan pada kemampuan berpikir tingkat tinggi. Penelitian ini dilakukan di SD berkategori tinggi skor AKM literasi membaca dan diharapkan menjadi best practice sekolah lain agar mengetahui prosedur pembelajaran literasi membaca di lapangan. Penelitian ini menggambarkan tahapan prabaca, membaca, dan pascabaca. Peneliti menggunakan pendekatan kualitatif dengan metode etnografi. Data diperoleh melalui observasi dan wawancara kepada kepala sekolah, guru, dan siswa kelas V. Data dianalisis melalui reduksi, disajikan tematik, dan disimpulkan. Secara keseluruhan, pelaksanaannya di kelas V SDN X belum sepenuhnya optimal. Sarannya guru agar lebih mengembangkan bahan ajar, mengulik strategi membaca, dan mengonsistensikan refleksi pembelajaran. Kata Kunci: Pembelajaran Literasi Membaca, Prosedur, Prabaca, Membaca, Pascabaca